A Personal Memoir: Fragments for an Autobiography - Tàpies, Antoni; Sobrer, Josep Miquel (Bloomington Indiana University Press, 2009)
A Personal Memoir: Fragments for an Autobiography integrates the memoirs of Antoni Tàpies, beginning in precivil war Barcelona and extending to Francoist Madrid, existentialist Paris, and New York in the 1950s, with historical images from diverse sources, including the family and the artist's archives. Tàpies's reflections on his interactions with such prominent cultural figures as Picasso, Miró, and Duchamp, on his approach to modernity and the avant-garde, and on the historical events of his lifetime from his birth in 1923 to the 1970s provide insights into the inner sources and development of his art. Highlighting the close ties between his writings and his visual work, this volume includes a generous selection of both color and black-and-white images that trace the unfolding of Tàpies's artistic language from the 1940s to the present.
Keywords: Biography